METAGENOMICS: UNRAVELLING THE UNCULTURED MICROBIAL COMMUNITY - HUSSEIN, IBRAHIM I. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
The discovery of the traditional culturing techniques for microorganisms in the laboratory has remained a classical landmark attained in the field of microbiology and sustained as the earliest methods used in the study of microbial physiology, functions and diversity by microbiologists. However, many studies now evidently portrayed these traditional culturing methods significantly unreflective of the uncultured microbial population. Thus, implying these historic microbiological techniques failing to capture the full spectrum of microbial diversity in an environment. Providentially, three decades ago, metagenomics has opened new avenues of research by enabling unprecedented analyses of genome heterogeneity and evolution in environmental contexts and providing access to far more microbial diversity than previously analysed. This new concept in microbial investigation has thrived in establishing the identity of microorganisms in diverse environments and allow a reasonable estimate of their functionality without the need for their cultivation. Metagenomics currently merged with the next-generation sequencing enabled the unravelling and functional exploitation of the uncultured microbial world, and conceivably transformed the archaic perception of microbial ecologists. Therefore, this review reflects on the traditional cultivation technique and the milestone attained since the dawn of metagenomics, with furtherance to the in-depth applications of the new age metagenomics approach in contemporary microbial studies, its challenges and future outlook.